Women's housing: balancing scaling and caring in three Canadian cities. Issue 2 (3rd April 2022) - Whitzman, Carolyn; Desroches, Marie-Ève
Abstract: Canada has recently enshrined the right to housing in legislation and included a funding target directed towards women-led households. Women's housing organisations are generally small and looking for ways to scale up while maintaining a care focus. This article describes potential impacts of these recent policy shifts, and how women's housing perspectives and practices might move from the periphery to the centre of policy-making.